The Role of Christian and Islamic Leaders to Strengthen Local Wisdom in Atambua - Yanuarius Seran (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Local wisdom is an ancestral heritage that is closely related to the life value that is not only formed into religion but also culture and traditions. The purpose of this study is to describe the local wisdom among representative leaders of religions in Atambua which contribute to maintaining a harmonious life. Traditional leaders, government officials, and religious leaders continue to renew local wisdom to maintain and preserve local wisdom, even though it is eroding and fading due to the negative influence of globalization and modernity. This paper is qualitative research featuring data from both fieldwork investigation, hybrid interview, and literature review. The findings of this study show that; First, Atambua local wisdom contributes significantly to true harmony and brotherhood; Second, localwisdom complements and strengthens the noble values of the Bible and the Qur'an; Third, the government and the traditional religious leaders play a role in inviting all parties to preserve religious harmony and creating dialogue forums to revitalize the local wisdom in Atambua. This article is the first grounded research to introduce indigenous proverbs such as knuk ida fatik ida and nekaf mese ansaof mese in the context of interfaith dialogue to encourage true intimacy and fraternity of "thy brother, who proceeded from the same womb" in Atambua.